Paciente femenino de 40 años de edad con cáncer de mama - Yilly Yaritha, Arana Veliz (2018)
The term cancer is used to define diseases that occur in cells where there is an abnormal growth of the same, which may eventually invade other organs and tissues, through lymphatic and blood tissue. The diagnosis is given by a specialized doctor, who is based on the interview, thorough physical examination, complementary studies such as mammography, ultrasound and a biopsy. It also requires self-exploration of the breast, since the woman can feel any change or abnormality, which allows you to see a doctor in a timely manner. When the response to the stimuli is negative, and does not help in the well-being of the person, the nurse plays an important role where the object of action is to help the person adapt to the new changes that arise in their environment, to achieve a better well-being in your health. To these stimuli Roy classifies them as focal, contextual and residual; when interpreting the person as a system, he defines two subsystems, those of primary processes (coping mechanisms) and those of secondary processes (adaptation mechanisms). Through adaptation modes the individual provides adaptive or ineffective responses, the former respond to the stimuli while the latter does not respond to the stimuli, this is where the nurse plays an important role since it must integrate the patient and the family to achieve inefficient responses disappear and achieve only adaptive responses. Therefore, the main objective of the nurse will be to establish adaptive responses.